2006
DOI: 10.3892/ijo.29.1.237
|View full text |Cite
|
Sign up to set email alerts
|

Leuprorelin acetate affects ERK1/2 activity in prostate cancer cells

Abstract: The mechanisms by which a GnRH analogue, leuprorelin acetate (LA), antagonizes the mitogenic effect of dihydrotestosterone (DHT) or epidermal growth factor (EGF) in prostate cancer cells is poorly understood. The mitogenactivated protein kinase system has a central role in growth regulation and, for this reason, we investigated the involvement of the extracellular signal-regulated kinase (ERK1/2) pathway in the response of both androgen-sensitive (LNCaP) and-insensitive (PC-3) prostate cancer cells to LA alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…In this paradigm, BRCA2 seems to function by exercising a stringent control upon cell proliferation capable of positive and negative feedback in the normal cellular environment, and its absence due to neoplastic cell transformation results in unchecked cell proliferation that is triggered by PI 3-kinase/ AKT signaling after cell interaction with the ECM. These results would support recent reports suggesting a role for activated ERK in mediating drug-induced apoptosis or inhibition of cell proliferation in PC-3, as well as ovarian and breast cancer cells (43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 91%
“…In this paradigm, BRCA2 seems to function by exercising a stringent control upon cell proliferation capable of positive and negative feedback in the normal cellular environment, and its absence due to neoplastic cell transformation results in unchecked cell proliferation that is triggered by PI 3-kinase/ AKT signaling after cell interaction with the ECM. These results would support recent reports suggesting a role for activated ERK in mediating drug-induced apoptosis or inhibition of cell proliferation in PC-3, as well as ovarian and breast cancer cells (43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 91%
“…The antitumor efficacy of GnRH agonists in peripheral tissues depends, amongst others, on the cross-talk with growth factor signaling cascades [21,24,39]. GnRH agonist direct inhibition of PCa growth acts by attenuating a well-documented autocrine proliferation signaling loop.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of studies on these cell lines, we have also demonstrated the ability of the GnRH agonist Leuprorelin acetate (LA) to downregulate PSA gene expression and to induce variations in apoptosis-related gene expression [18][19][20]. More recently, the ability of LA to counteract the EGF-induced ERK1/2 activation in LNCaP cells has been demonstrated by our group [21].…”
Section: Introductionmentioning
confidence: 94%
“…In fact, antagonistic effects were observed on tumor cell growth as well as on the expression of PsA, MAP kinases, apoptosis-related genes and GnRH-R (22)(23)(24)(25)(26)(27)(28)(29). The molecular basis of the interference between DHT and LA is still unclear but conceivably could be ascribed to the analogue targeting of the androgen receptor (AR) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, GnRH agonists are ineffective in regulating cell growth when used alone, but they counteract or suppress the stimulation of cell proliferation induced by estrogens in mammary and endometrial cancer cells (22)(23)(24) and by androgens or epidermal growth factor (EGF) in CaP cells (25). In the same CaP cells, we demonstrated the ability of the GnRH agonist, leuprorelin acetate (LA), to modulate the expression of various genes and/or proteins correlated with growth, differentiation and apoptosis and to up-regulate GnRH-R (25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 92%